Contribution Fisheries Management of Conservation to Society 5.0 - Fithor, Alin; Nugroho, Beni Sabdo (Indonesian Fisheries Research Journal, 2024)
Mangunharjo Beach in Semarang, Indonesia, is a popular coastal destination known for its beautiful scenery and recreational activities, which focus on integrating technology and innovation for the betterment of society. Some potential contributions are (1) Smart City Integration and (2) Community Engagement. By embracing these contributions, creating a sustainable and inclusive destination leverages technology for the betterment of visitors and the local community. The availability of technologies and their broad humanitarian applications allow economically strong countries to create a comfortable living environment and gain a leading position in the practical propagation for best conservation with fisheries management of Society 5.0, which takes place in Mangunharjo Beach and its area; it becomes an integral part of the country.Beach, Contribution, Mangunharjo, Society, Conservation